An Analysis of Indonesian Spelling Errors in Fable Compositions of Class VII Students at Daarul Muqimien Middle School (2019/2020 Academic Year) - Indarti, Fifik; Yani, Juli (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This study aims to describe the form of general guideline errors in Indonesian spelling contained in the fable compositions of class VII students of Daarul Muqimien Middle School, Sukadiri, in the 2019/2020 academic year. This researcher used a qualitative approach with a descriptive method. The subject of this study was the fable texts of class VII students of Daarul Muqimien Middle School. The results of this study are as follows. First, the number of errors in the use of puebi contained in students' writing skills or compositions. The form of general guideline errors in Indonesian spelling (PUEBI) is divided into five aspects, namely errors in the use of capital letters, use of periods, use of commas, use of question marks, use of exclamation marks. From these five aspects, the following results were found; (1) errors in the use of capital letters as many as 47 cases of errors, (2) errors in the use of period punctuation as many as 21 cases of errors, (3) errors in the use of comma punctuation as many as 27 cases of errors, (4) errors in the use of question marks 6 cases of errors, (5) errors in the use of exclamation punctuation as many as 9 cases of errors. Second, From the percentage of errors, errors in the use of capital letters are the most dominant errors made by students, reaching 47 cases of errors. Furthermore, the least frequent error is the error in the use of question marks which reaches 6 cases of errors. From the results of the study, researchers can recommend an understanding of spelling and punctuation in learning so that this learning can improve student learning outcomes.